2019
DOI: 10.1007/s41999-019-00162-8
|View full text |Cite
|
Sign up to set email alerts
|

EuGMS Task and Finish group on Fall-Risk-Increasing Drugs (FRIDs): Position on Knowledge Dissemination, Management, and Future Research

Abstract: Falls are under-recognized as adverse drug events. Healthcare professionals are reluctant to withdraw fall-risk-increasing medications. The EuGMS Task and Finish group on fall-risk-increasing drugs (FRIDs) proposes in this paper its recommendations on dissemination of knowledge about, management of, and future research on FRIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
0
16
0
5
Order By: Relevance
“…Previous studies have reported cardiovascular and psychotropic medicines as the most common medications in the FRIDs [13][14][15][16][17][18][19]. Although more than threequarters of the pharmacists in our study knew antihypertensives could cause a fall and orthostatic hypotension, however most could not specifically relate other drugs such as antipsychotics, anticholinergics and antidiabetics as risk factors for fall and orthostatic hypotension.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Previous studies have reported cardiovascular and psychotropic medicines as the most common medications in the FRIDs [13][14][15][16][17][18][19]. Although more than threequarters of the pharmacists in our study knew antihypertensives could cause a fall and orthostatic hypotension, however most could not specifically relate other drugs such as antipsychotics, anticholinergics and antidiabetics as risk factors for fall and orthostatic hypotension.…”
Section: Discussionmentioning
confidence: 58%
“…The main instrument used for data collection was a structured questionnaire developed by the investigators following extensive review of relevant studies [5,8,13], as well as employing previous experience. The questionnaire consisted of four sections.…”
Section: Data Collection Instrumentmentioning
confidence: 99%
See 3 more Smart Citations